Atypical presentation of Niemann-Pick disease - Keshavamurthy, Mysore Lakshmikantha; Basavaraja, G V; Rajeshekarmurthy, G R; Sanjay, K S; Premalatha, R (Indian Journal of Child Health, 2015)
Niemann-Pick (NP) disease is a distinct disorder with specific clinical and morphological manifestations. We report a 2-year-old girl who presented with normal development, acute onset of pallor, lethargy, and massive splenomegaly, which made us to think of hemolytic anemia as the initial diagnosis. Her bone marrow done, after initial hematological work up being normal, showed NP cells. As the child did not have any neurological abnormality, she was diagnosed as NP Type B (NPD-B) storage disease. We report it as a typical presentation of NPD-B.